The essential Ken Blanchard collection. (FTPress Delivers, 2011)
<Lt;lt;p>gt;gt;<lt;lt;i>gt;gt;<lt;lt;b>gt;gt;A brand new collection of essential insights for your business and career from world-renowned experts ... now in a convenient e-format, at a great price!<lt;lt;/b>gt;gt;<lt;lt;/i>gt;gt;<lt;lt;/p>gt;gt; <lt;lt;p>gt;gt;<lt;lt;b>gt;gt;Extraordinary techniques for "Leading at a Higher Level"--Ken Blanchard and two of the world's most successful business leaders!<lt;lt;/b>gt;gt;<lt;lt;/p>gt;gt; <lt;lt;p>gt;gt;Get 30+ years of Ken Blanchard's breakthrough leadership techniques--and see how great leaders apply them! <lt;lt;i>gt;gt;Leading at a Higher Level<lt;lt;/i>gt;gt; guides you through developing high-performance organizations and teams. In <lt;lt;i>gt;gt;Helping People Win at Work<lt;lt;/i>gt;gt;, Blanchard and WD-40's Garry Ridge help you Partner for Performance with every employee. In <lt;lt;i>gt;gt;Lead with Luv<lt;lt;/i>gt;gt;, Blanchard and Southwest Airlines' Colleen Barrett help you achieve amazing results by leading with love!<lt;lt;/p>gt;gt; <lt;lt;p>gt;gt;<lt;lt;i>gt;gt;From world-renowned organizational leaders and innovators <lt;lt;b>gt;gt;Ken Blanchard<lt;lt;/b>gt;gt;, <lt;lt;b>gt;gt;Garry Ridge<lt;lt;/b>gt;gt;, and <lt;lt;b>gt;gt;Colleen Barrett<lt;lt;/b>gt;gt;.<lt;lt;/i>gt;gt;<lt;lt;/p>gt;gt.